Burocracia de médio escalão e política de esporte universitário: o caso da implementação em uma universidade pública - Santos, Erasmo Braz dos (Universidade do Vale do Rio dos Sinos, 2025)
The Middle Level Bureaucracy (MLB), which is intermediate to the state, is little studied as an object of analysis. Implementation, the locus of its action, has some policy content, such as university sport (US), which receives little attention from national policy. Therefore, this study aimed to explain how the BME acted, how it influenced the content of public policy (PP) and what this meant in an implementation context with little regulation and funding. The general objective of the research was to analyze, in the period from 2003 to 2022, how the actions of the MLBs affected the implementation of US as a PP content in a Brazilian federal public university in a context of little regulation and funding. The specific objectives were to understand the historical trajectory and the changes that culminated in the implementation of the US as PP content; to map and understand aspects of the structure of local US implementation in the period under study; and to contribute to the analytical debate on the MLB role as a bureaucratic actor in implementation. Structural and relational analytical lenses were used, as well as documentary research and semi-structured interviews, in addition to the data analysis technique of thematic categorical content analysis. The empirical case was a federal university in the midwest region. MLBs, academics/athletes and presidents of the university sports federation were interviewed. There was evidence that the US created by academics/athletics did not find institutional support and perished. The MLB, an incidental actor, with an individual biography linked to sport in the institution, took on this role and, in a context of little regulation, used its autonomy and discretion, built an instrument (standards of action) that became an internal norm and sought funding via interactions with the top echelon, making it possible for the US to operate permanently. Also using its technical-political and technical-managerial characteristics, it both operationalized and acted in a political way to guarantee gains for the PP content. However, there was no collective grouping, which made it difficult to analyze its performance on an ideational level. It remained close to the direct actors and managed to legitimize a centrality (even if not thought of) through shared values. His relationships went beyond implementation and reached actors inside and outside the institution, overcoming structural constraints, even though the direct and surrounding actors were the ones who were most closely involved. In this way, the MLB work on implementation has shown that implementation does not come from the norm alone, that it is possible to institutionalize certain instruments within a favourable institutional context and that individual biography also contributes to this.
Keywords: Atores; Interações; Padrões de ações; Centralidade; Esporte universitário; Actors; Interactions; Action patterns; Centrality; University sport; ACCNPQ::Ciências Humanas::Sociologia